Modic changes in the lumbar vertebral column of chondrodystrophic and non-chondrodystrophic dogs with intervertebral disc disease - Agustini, Dyah; Heimann, Mary K.; Co, Megan; Walter, Benjamin A.; Purmessur, Devina; Moore, Sarah A. (Frontiers in Veterinary Science, 2024)
Modic changes (MC) are signs of vertebral pathology visible on magnetic resonance (MR) images that have been associated with low back pain (LBP) and disc degeneration in people. Multiple breeds of dogs also develop MCs and coincident back pain. However, the association between breed, MC, and spinal pathologies has yet to be fully elucidated. This study aimed to identify the prevalence of MC that occur spontaneously in the lumbar vertebral column of dogs diagnosed with intervertebral disc disease (IVDD) and examine their association with demographic criteria and the disc width index (DWI). Medical records and lumbar vertebral column MR images were examined from 104 dogs (831 intervertebral disc spaces and adjacent vertebrae), which were divided into three groups: chondrodystrophic dogs (CD; n= 54) and non-chondrodystrophic dogs (NCD; n= 30) with IVDD as the primary diagnosis, and control dogs (n= 20) with other spinal diseases as their primary diagnosis. Results demonstrate increasing age and a diagnosis of IVDD were significantly associated with MC in dogs (p< 0.001 and p= 0.0062, respectively). In CD dogs with IVDD, Type 2 MC were most prevalent, whereas, in NCD dogs, Type 3 MC were the most prevalent type. Type 2 MC were distributed nearly equally across the lumbar vertebral column, while Type 3 MC were primarily detected at the level of L7-S1. This study demonstrated that MC developed spontaneously in dogs, are common in dogs diagnosed with IVDD, and the type observed varies by breed. Further research is needed to understand the pathogenesis of MC; however, the increased presence of Type 2 MC in CD dogs, similar to what is found in people with disc degeneration, suggests that CD dogs could serve as models for MC in people.